2020
DOI: 10.4025/actascibiolsci.v42i1.51151
|View full text |Cite
|
Sign up to set email alerts
|

Central cellular signaling pathways involved with the regulation of lipid metabolism in the liver: a review

Abstract: The liver is primarily responsible for energy homeostasis and the regulation of lipid, carbohydrate and protein metabolism. Lipid metabolism consists of distributing lipids to peripheral tissues or ensuring their return to the liver to be reprocessed. Additionally, cellular metabolism is regulated by several molecules in different signaling pathways. Lipid homeostasis in the liver is mainly regulated by AKT, AMPK, SREBP, PPAR, and JNK. The PI3K/AKT/mTOR signaling pathway results in the biosynthesis of macromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In this respect, our results showed a remarkable defect in the insulin signaling pathway manifested by the downregulated expression of IRS, PI3K, PDK1, and AKT with a concomitant upregulated expression of the nuclear FoxO1 which in turn activated the G6Pase a downstream target that promoted gluconeogenesis. These results agree with that of both Dwivedi et al 30 and Lopes et al 51 who reported that the status of insulin resistance is accompanied with the inhibition of the PI3K/AKT through FOXO1 activation promoting gluconeogenesis and thus hyperglycemia. Furthermore, Li et al 8 reported that the protein levels of PI3K and Akt in the liver of NAFLD were decreased while their activation would promote liver regeneration and suppress the progression of NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, our results showed a remarkable defect in the insulin signaling pathway manifested by the downregulated expression of IRS, PI3K, PDK1, and AKT with a concomitant upregulated expression of the nuclear FoxO1 which in turn activated the G6Pase a downstream target that promoted gluconeogenesis. These results agree with that of both Dwivedi et al 30 and Lopes et al 51 who reported that the status of insulin resistance is accompanied with the inhibition of the PI3K/AKT through FOXO1 activation promoting gluconeogenesis and thus hyperglycemia. Furthermore, Li et al 8 reported that the protein levels of PI3K and Akt in the liver of NAFLD were decreased while their activation would promote liver regeneration and suppress the progression of NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…As first formulated in 1963 by Randle et al as a general principle, glucose and free fatty acids are competing substrates of cellular metabolism [ 29 ]. This antagonism is not limited to metabolic regulation at the enzyme level but is also realized in the activation of different groups of transcription factors and their associated signaling pathways [ 30 , 31 ]. Whereas steatosis and the resulting NASH are linked to elevated plasma levels of free fatty acids, IR and diabetes are linked to elevated plasma levels of glucose.…”
Section: Discussionmentioning
confidence: 99%